Does the universal adaptive strategy theory apply to natural regeneration in heterogeneous subtropical karst forests? - Yang, Zeyu; Wu, Yuhang; Chen, Shiren; Sui, Mingzhen; Zhang, Guangqi; Liu, Qingfu; Chen, Danmei; He, Yuejun; Zang, Lipeng (Ecological indicators, 2024)
•This study involved main regeneration stages of degraded karst forests.•Apply the universal adaptive strategy theory to heterogeneous karst forests.•The biotic factors contribute more to the ecological strategy spectrum. The universal adaptive strategy theory (UAST) describes how the ecological strategy of plants changes along the succession after disturbance. However, whether it applies to those off-peak successional pathways in extremely heterogeneous forests is uncertain. This study established a series of forest dynamic plots along the natural regeneration in subtropical karst forests, and aimed to verify whether UAST applied to the succession in extremely heterogeneous forests. By measuring the dominant plant functional traits (PFTs) and quantifying the plant ecological strategy spectrum, we found that the PFTs varied significantly along the natural regeneration, as did plant ecological strategies. Further results showed that the C- and S-strategy dominated the community-level ecological strategy spectrum. In addition, the C-strategy gradually increased along the natural regeneration, while the S-strategy exhibited a decreasing trend. The community spatial structure and abiotic factors including soil physicochemical properties and topographic factors jointly drove the ecological strategy spectrum of the plant community, with the community spatial structure playing a more important role. This study provided clear evidence to support Grime’s CSR theory and the UAST, which emphasized the abiotic stress conditions supported the S-strategy plants, while the C-strategy would dominate in relative fertile soil conditions.